Banking Services versus Mobile to enhance Financial Inclusion in Algeria -A Case Study of the National Bank of Algeria- - djenhi, massika; boudah, abdeljalil (Journal of Research in Finance and Accounting, 2024)
This study aims to highlight the contribution of banking services in promoting financial inclusion in Algeria through the delivery of financial services using mobile phones and making them accessible to different segments of society, especially marginalized, low-income, and rural populations. Using a descriptive analysis and case study approach, the study concluded the importance of the tool used by the bank to develop and promote financial inclusion, despite the constraints inherent in the Algerian banking system. Finally, some suggestions have been proposed that may benefit Algeria's interest in supporting and developing financial inclusion in the banking sector.